Effects of Light Intensity and Wavelength on the Phototaxis of the Crassostrea gigas (♂) and Crassostrea sikamea (♀) Hybrid Larvae - Zhang, Xuekai; Fan, Chao; Zhang, Xingzhi; Li, Qiongzhen; Li, Yangchun; Wang, Zhaoping (Frontiers in Marine Science, 2021)
Light sensitivity is important for marine benthic invertebrates, for oysters, it plays a vital role in their settling phase. Generally, the emerging of oyster eyespot is a signal of larvae settling, while like most of the other coastal species, oysters were highly threatened by artificial light pollution. Therefore, we investigated the phototaxis of the eyespot larvae and eyeless larvae for the C. gigas (♂) and C. sikamea (♀) hybrid under different light intensities and wavelengths to understand how light affects the behaviors of the artificial hybridization oyster. The results show that the hybrid larvae have positive phototaxis to specific light intensity and wavelength. We give a further conclusion that 5lux intensity light is the positive phototaxis light for the hybrid eyeless oyster larvae; after the eyespot appears, the acceptable light intensity range of hybrid larvae is expanded to 5lux-10lux, but no higher than 15lux; while light intensity exceeds 25lux will cause negative phototaxis. The present study also suggests the potential positive effects of the green light on oyster larvae gathering and larvae settling inducing function of the red light. In conclusion, our study may contribute to the understanding of oyster hybrid phototaxis and settling, as well as the further perspective of light pollution on the benthic communities and guiding the coastal system restoration.